Preserving mental health - Melgosa, Julián (2017)
When talking about physical health, almost everyone knows what needs to be done to preserve it. But when we ask how to maintain good mental health, many doubt and do not know what to say. However, it is possible to regulate our mental and emotional well-being, influencing our thoughts, feelings, desires and mood. It is possible to make decisions of the utmost importance for mental health. And reaching those decisions, we will enjoy a balanced state of mind and achieve our goals. In addition, we will be preventing anxiety, discouragement, guilt, the feeling of inferiority and many other ailments of the psychic nature. In this essay, the reader will find a series of practical and simple application tips to enjoy peace of mind.